Thoracic Ultrasound in Assessment of the Pleura in Connective Tissue Disease - Diktaş Tahtasakal, Serap; Doğan, Coşkun (Archives of Rheumatology, 2025)
Background/Aims: To investigate the use of thoracic ultrasound (US) in the assessment of the pleura in connective tissue disease (CTD). Materials and Methods: The clinical, radiologic, and demographic data were recorded from patients who were diagnosed as having CTD at least 1 year before the study. Thoracic US was performed for pleural assessments in all patients who met the inclusion criteria. The thickness of the parietal and visceral layers of the pleura and pleural space was measured in millimeters and recorded in both the CTD and healthy control groups, and data from the CTD group were compared with those from the healthy control group. Results: A total of 86 participants, 44 (51.2%) with CTD and 42 (48.8%) healthy volunteers, were included in the study. There were 37 (84.1%) females with a mean age of 55.1 ± 11.1 years in the CTD group and 23 (54.8%) females with a mean age of 56 ± 11.8 years in the control group. In the CTD group, the mean parietal pleural thickness, visceral pleural thickness, and pleural space were 0.61 ± 0.16 mm, 0.61 ± 0.17 mm, and 0.77 ± 0.5 mm, respectively, and in the control group, these values were 0.42 ± 0.08 mm, 0.44 ± 0.09 mm, and 0.47 ± 0.15 mm, respectively (P < .001). Conclusion: Pleural thickness was increased in patients with CTD compared with healthy controls. The lungs are among the target organs in CTD, and US is a non-invasive and radiation-free imaging modality that can be used in the assessment of pleural involvement. Cite this article as: Diktaş Tahtasakal S, Doğan C. Thoracic ultrasound in assessment of the pleura in connective tissue disease. Arch Rheumatol. 2025;40(4):474-481.